Сooperation of Russian and Spanish Researchers Facing the Challenges of Time - I. V. Krivushin (Ибероамериканские тетради)
Book Review: Spain and Russia Facing the Challenges of Time. O. Volosyuk (ed.), — Moscow:  Mezhdunarodnye otnoshenia, 2022. — 648 p.